Heterogeneous embankment dam under rapid drawdown - Aldungarova Aliya; Mkilima Timoth; Utepov Yelbek; Tulebekova Assel; Zharassov Shyngys (Magazine of Civil Engineering, 2023)
Loading conditions are among the significant determinants of the stability of embankment dams: they need to be carefully investigated during the design phase of the dam construction. Unfortunately, it is almost impossible to investigate the combination of these parameters in-situ. In the current work, the influence of rapid drawdown loading conditions on the stability of the embankment dam was investigated with the help of numerical modeling for a case of the Aktobe dam in Kazakhstan. The seepage analyses were carried out concurrently with slope stability analyses. Mainly, five different drawdown cases were investigated, which are: steady-state, instantaneous drawdown, 5-days drawdown, 10-days drawdown, and 1m per day drawdown rate. In terms of flow type, both steady-state and transient flow conditions were investigated. In general, when the embankment was subjected to the 1 m per day drawdown rate a minimum factor of safety value of 1.486 was retrieved from computations. The factor of safety value is equivalent to a 3.7 % increase from the 10 days drawdown rate, 8.3 % from the 5 days drawdown rate and 48.6 % from the instantaneous drawdown.